2019
DOI: 10.5114/ait.2019.86275
|View full text |Cite
|
Sign up to set email alerts
|

Validation of APACHE II and SAPS II scales at the intensive care unit along with assessment of SOFA scale at the admission as an isolated risk of death predictor

Abstract: The first scales evaluating the patient conditions were designed in the 80-ties of the previous century and quickly became popular at intensive care units (ICUs) [1, 2]. Since that time, numerous new scales have been created or the existing ones modified in order to provide most accurate assessment of patients. They are the tools for validation of the therapeutic procedures used as well as for monitoring the quality and costs of treatment. The standardised assessment measures are also extremely useful during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 16 publications
(34 reference statements)
0
31
0
6
Order By: Relevance
“…In addition, we also found that TGF-b1 gene rs1800469 locus T > C and rs1800470 C > T were associated with lower APACHE II score and SOFA score, whereas rs1800468 G > A as well as rs1800471 C > G were related to higher APACHE II score and SOFA score. We know that the APACHE II score and SOFA score are commonly used condition assessment tools for clinically critical patients (Choi et al, 2018;Kadziolka et al, 2019). This suggests that these genetic factors play a very important role in the occurrence and severity of sepsis, and analysis of the correlation between these SNP loci and plasma TGF-b1 levels may be very useful in revealing the reasons for this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that TGF-b1 gene rs1800469 locus T > C and rs1800470 C > T were associated with lower APACHE II score and SOFA score, whereas rs1800468 G > A as well as rs1800471 C > G were related to higher APACHE II score and SOFA score. We know that the APACHE II score and SOFA score are commonly used condition assessment tools for clinically critical patients (Choi et al, 2018;Kadziolka et al, 2019). This suggests that these genetic factors play a very important role in the occurrence and severity of sepsis, and analysis of the correlation between these SNP loci and plasma TGF-b1 levels may be very useful in revealing the reasons for this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Both CRS and rHLH can manifest as ARDS and have a similarly hyperactive immune response. Although APACHE II scores are useful in predicting mortality in patients in the intensive care unit [ 2 ], we sought a risk assessment for less critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of case reports have been published describing coronavirus disease 2019 (COVID-19) infections in solid organ transplant recipients, few have explored formulas to predict the hospital course of this high-risk patient group. Because outcomes have ranged from mild infection [ 1 ] to death due to acute respiratory distress syndrome (ARDS) and cytokine release storm (CRS), in the severe COVID-19 cases [ 2 ] we explored the utility of a risk stratification score that could help predict outcomes in these patients. We decided to implement the H-Score, the first validated score developed for the diagnosis of reactive hemophagocytic lymphohistiocytosis (rHLH) [ 3 ].…”
mentioning
confidence: 99%
“…20,21 APACHE II and SOFA scores have recently been externally validated in a single-center Polish study; recalibration was not performed. 22 Preliminary data from the Silesian registry of intensive care units showed a standardized mortality ratio for APACHE II of 0.93. No formal discrimination or calibration test was presented.…”
Section: Methodsmentioning
confidence: 99%